Problems of Ensuring Collective Security of the Post-Soviet Space in the Context of International Escalation - D. L. Tsybakov (Проблемы постсоветского пространства)
The relevance of this study lies in the need to study the potential effectiveness of the Collective Security Treaty Organization in the conditions of the world order in the XXI century. The formation of the collective security system of the post-Soviet space was accompanied by a number of crisis processes determined by the post-bipolar era. Based on the results of the review of the activities of the CSTO institutions, the reasons for the insufficient effectiveness of the collective security system in the situation of modern international escalation are determined and further reformatting of the scope of competence and structure of the organization is predicted.